Why do Prices Change? An Analysis of Supply and Demand Shifts and Price Impacts in the Farmed Salmon Market - Brækkan, Eivind Hestvik (UiT The Arctic University of Norway, 2014)
The papers of this thesis are not available in Munin: 1. Brækkan, Eivind Hestvik & Thyholdt, Sverre Braathen: 'The Bumpy Road of Demand Growth – An Application to Atlantic Salmon' (manuscript) 2. Brækkan, Eivind Hestvik: 'Disentangling supply and demand shifts: the impacts on world salmon prices' (manuscript) 3. Brækkan, Eivind Hestvik,. Thyholdt, Sverre Braathen & Myrland, Øystein: 'The Demands They Are a-Changin’' (manuscript) Price changes in any market are essentially due to shifts in supply relative to demand. In a global market there can be several simultaneous supply and demand shifts in different geographical locations, all affecting prices to different extents. This dissertation focuses on procedures for measuring such shifts and their relative effects on prices by looking at the global market for farmed salmon in the period between 2002 and 2011. Farmed salmon is a relatively homogeneous, globally traded product whose market size has burgeoned over the last 30 years. The first paper determines the magnitude of the shifts in annual demand across all salmon-importing regions. Results indicate that demand varies considerably between years and regions and does not appear to follow a smooth trend - as usually assumed in empirical demand analysis. The second paper uses the same approach to determine the size of annual regional supply and demand shifts from exporting and importing regions. The impacts of these shifts on prices are determined through an Equilibrium Displacement Model. This allows the decomposition of annual price movements into the effects of regional supply and demand shifts. We find large variation in supply and demand shifts and price impacts between regions and within regions over time. The third paper extends the procedure of the first. We disentangle the impacts from income growth and price changes in substitute products from the total demand shift. The remaining, residual shift in demand is due to other, unknown or omitted factors. Results indicate demand shifts due to unknown ...